Write Us into the Story: Archives and Archivists in Narratives for Children - Sweeney, Shelley; Avery, Cheryl (Archivaria, 2021)
Archivists need to increase public understanding, support, and engagement in archives to enable archives to fulfil their missions. As one way to increase support, archives have increasingly carved out time and resources for various types of outreach. One important audience that has long been acknowledged is children. In the past, archivists have visited classrooms, brought children to archives, and prepared kits of archival facsimiles or surrogates on websites for children to use with the guidance of teachers. But another way to reach children includes narratives in books, films, and television directed at children. This article explores a number of titles to see whether archives and archivists are accurately portrayed in the narratives. The numbers are few, and the portrayals are generally weak. Two exceptions were books created by an archivist and commissioned by an archives. These two approaches led to significant works that enhance children’s understanding of archives and archivists and lead the way as examples for future archival endeavours to emulate.